Baseline Carotid Intima-Media Thickness and Stroke Recurrence During Secondary Prevention With Pravastatin. Issue 6 (June 2019) - Wada, Shinichi; Koga, Masatoshi; Minematsu, Kazuo; Toyoda, Kazunori; Suzuki, Rieko; Kagimura, Tatsuo; Nagai, Yoji; Aoki, Shiro; Nezu, Tomohisa; Hosomi, Naohisa; Origasa, Hideki; Ohtsuki, Toshiho; et al.
Abstract : Background and Purpose—: As a prespecified post hoc analysis of the J-STARS (Japan Statin Treatment Against Recurrent Stroke) Echo Study, the 5-year stroke recurrence rate according to the baseline mean carotid intima-media thickness (IMT) with and without pravastatin treatment was investigated. Methods—: Patients were randomly assigned to receive pravastatin 10 mg/day (pravastatin group) or control group (nonstatin treatment; 1:1) for 5 years. Baseline mean IMT of the common carotid artery was measured by ultrasonography. Cox proportional hazards models were used to investigate whether the stroke (any ischemic stroke, atherothrombotic brain infarction, or lacunar infarction) recurrence rate was different according to tertiles of baseline mean IMT. Results—: A total of 793 patients, including 388 in the pravastatin group and 405 in the control group, were investigated. In the control group, Cox proportional hazards models showed that participants in the highest tertile IMT group (≥0.931 mm) had a higher rate of atherothrombotic brain infarction than those in the lowest tertile IMT group (<0.812 mm; [hazard ratio, 9.08; 95% CI, 1.15–71.43]). Patients in the pravastatin group had a lower risk of atherothrombotic brain infarction than those in the control group only in the highest tertile IMT group by the log-rank test ( P value=0.045). Conclusions—: Long-term pravastatin administration may prevent the occurrence of atherothrombotic brain infarction in noncardioembolic infarction patients with the highest tertile IMT. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00361530. Abstract : Supplemental Digital Content is available in the text.